Sakralmöbel aus Österreich: Von Tischlern und ihren Arbeiten im Zeitalter des Absolutismus. I: Östliche Landesteile - Bohr, Michael (2017)
The study includes picture sources and written records to fully discuss the history of ecclesiastical interiors as well as the stylistic development of the furnishings in the early modern period. In addition, the study explores aspects relating to the social and economic history.